Study on the characteristics of carotid wall shear stress in type 2 diabetes patients based on ultrasound vector flow imaging - Li, Zhaohuan; Luo, Anguo; Liu, Xuebing; Xie, Shenghua; Wang, Yulin; Deng, Lan; Zhong, Shimin; Liu, Yaoxia; Cao, Xu; Du, Yigang; Luo, Wen; Deng, Yan; et al. (Frontiers in Endocrinology, 2024)
Objectives: We aimed to quantitatively analyze wall shear stress (WSS) of the common carotid artery (CCA) and elucidate the relationship between WSS and cardiovascular disease (CVD) in patients with type 2 diabetes mellitus (T2DM) using ultrasound vector flow (V-Flow) imaging.Methods: A total of 109 T2DM patients were selected as the DM group, while 49 healthy volunteers served as the control group. V-Flow examination of the bilateral CCA was conducted. The maximum wall shear stress (WSSmax) and mean wall shear stress (WSSmean) at the bifurcation, proximal bifurcation and middle segment of the bilateral CCA were obtained.The DM group showed decreased WSSmean in the middle region and proximal bifurcation of the CCA compared with the control group (p < 0.05). The WSSmean was further decreased in T2DM patients with CVD compared to those without CVD (middle region: 0.71 ± 0.17 Pa vs. 0.84 ± 0.24 Pa, p < 0.05; proximal bifurcation: 0.62 ± 0.22 Pa vs. 0.80 ± 0.21 Pa, p < 0.05). The receiver operating characteristic curve showed that a model combining with age, body mass index and WSSmean at the proximal carotid bifurcation had diagnostic value for detecting CVD in T2DM patients (area under the curve: 0.862, p < 0.05).WSSmean has potential value for evaluation of atherosclerosis, as well as in detecting the occurrence of CVD in T2DM patients. Ultrasound V-Flow imaging may be an effective tool for non-invasive evaluation of WSS in the clinic.